ANALYSIS OF IMIS'S SUCCESS ON TEACHER PERFORMANCE AND ORGANIZATIONAL PERFORMANCE IN VOCATIONAL SCHOOLS (Journal of Information System Management (JOISM), 2024)
This paper aims to analyze the factors that influence individual and organizational performance regarding the use of an Internship Management Information System (IMIS), which is named the SIM-PKL application for the internship program at SMK Negeri 11 Malang, with a framework in the DeLone and McLean Information Systems Success Model (ISSM). A quantitative method was employed, gathering data from SIM-PKL users. The sample comprised 55 respondents: 9 coordinators, 30 vocational teachers, and 16 general subject teachers. The analysis identifies key success factors, including system quality, information quality, service quality, intention to use, satisfaction, individual performance, and organizational performance. The findings align with the Delone & McLean framework, which evaluates information system success. Further analysis revealed a significant direct influence of system quality, information quality, and service quality on usage intentions and user satisfaction, while the net benefits (individual and organizational performance) were not statistically significant. Intention to use and user satisfaction are able to significantly mediate the influence of system quality, information quality, and service quality on net benefits. Intention to use and user satisfaction are important to increase system usage, enhance productivity, and positively affect performance. This study contributes to understanding SIM-PKL to guide schools in enhancing their management information systems.